Indian banks,their portfolios,profits,and policy (Fort,Bombay : T.V.Chidambaran, 1964)
The book tries to break new ground in the field of empirical investigations on Indian monetary issues
Includes bibliographical references
obn21/01/2019
Loans
Keywords: Banks and Banking-india; Monetary policy-India; Banks and banking